Advancements and challenges in methodological approaches for game-based health interventions: a scoping review - Glass, Shaina; Galati, Alexia (Frontiers in Digital Health, 2025)
IntroductionApplying game design techniques to create engaging health interventions has become more common, though still met with challenges and criticisms. This scoping literature review evaluates the extent to which recent health-based game intervention studies have improved from past criticisms around the process of game development, theoretical grounding, and implementation in terms of research design.MethodsFollowing a search of relevant databases and an AI tool (Elicit.org), 26 published articles met our selection criteria of reporting a game-based health intervention task developed by the article's authors. In each article, the reported theoretical grounding, use of game mechanics, and methodologies for developing and implementing game-based interventions were assessed. Our procedure involved coding for psychological or game design theories, game mechanics, and the research methods and design approaches used for intervention development. We reasoned that articles grounded in theory would be more likely to report effective methodologies and support for their design choices.ResultsOur findings revealed that authors frequently used quantitative methods to determine intervention impact, explicitly referenced psychological (vs. game design) theory more frequently, and used more than one game mechanic in the interventions. In line with recommendations, the majority of studies used large sample sizes and applied their interventions in real-world settings.DiscussionDespite these improvements, we identified areas of growth: utilizing interdisciplinary teams, user-centered and iterative approaches, and standardizing the reporting of intervention design components. This review is intended to inform the future of applied game design in health contexts.